Improving Junior High School Students’ Reading Comprehension Skill through Flipbook - Wilia Astuti; Lusi Nurhayati; Yuyun Yulia; Pelin Derinalp (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2026)
Reading is an essential part of the language learning process that enables students to obtain. information and to expand their language knowledge. In the current era of technology, there is a need for learning media that is interesting and effective to improve students’ reading comprehension. Flipbook as one of digital learning media provides many advantages to implement. This study aimed (1) to explain how the use of Flipbook can improve students’ reading comprehension skills and (2) to analyze the changes in students’ reading comprehension after the implementation of Flipbook. Utilizing a cyclical Classroom Action Research (CAR) model, the research was conducted over two cycles involving planning, acting, observing, and reflecting. The research participants were 31 nineth grade students of junior high school. The data were collected and analysed using both qualitative and quantitative methods. The findings demonstrated positive improvement in students’ reading comprehension and engagement after the implementation of Flipbook. Cycle 1 showed that the students felt easier to understand the text using Flipbook. It helped students to visualize the story. Whereas in cycle 2, the positive aspects were identified. Students had better comprehension in reading text on Flipbook. The implementation in cycle 2 was better because it had well-preparation and the text was adjusted to the students’ need and level. This study concluded that Flipbook is an interactive and effective tool to improve reading comprehension in junior high school.